Transmission of environmentally responsible behavior between tourist destination employees and tourists: The role of moral elevation and environmental knowledge - Ye, Weijiao; Li, Ziqiang; Xu, Yuyan (Frontiers in Psychology, 2022)
Introduction Tourists’ environmental misconduct is the primary reason for the environmental destruction that tourist sites experience; nevertheless, their environmentally responsible behavior is also a major push for the improvement of the environment. The main goal of this study is to induce tourists to adopt proactive environmental responsibility behaviors. Methods A total of 455 valid questionnaires were obtained from China and analyzed using multiple linear regression. Results The findings of this study indicate employees’ environmentally responsible behavior (E-ERB) in tourist destinations has a positive impact on tourists’ environmentally responsible behavior (T-ERB). In the mediating variable of moral elevation, the correlation between E-ERB and T-ERB is mediated by elevating emotions and views of humanity. And desire to be a better person did not play a mediating role in the relationship between E-ERB and T-ERB. Additionally, environmental knowledge moderates the transmission path of the impact of E-ERB and T-ERB via elevating emotions. With high environmental knowledge, the transmission path of the impact of employees’ environmentally responsible behavior of the tourist destination on tourists’ environmentally responsible behavior via elevating emotions will be enhanced. Discussion We propose a new perspective to explain the transmission mechanism between employees’ environmentally responsible behavior and tourists’ environmentally responsible behavior in tourism destinations, which will help to expand our understanding of the relationship between employees’ behavior and tourists’ behavior. We expect our study to spark more exploration of the contagion of positive behavior in the field of environmental psychology.